2020
DOI: 10.1152/ajpendo.00310.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conditioned media from murine lung cancer cells and human tumor cells on cultured myotubes

Abstract: Factors secreted from tumors/tumor cells are hypothesized to cause skeletal muscle wasting in cancer patients. We examined whether cancer cells secrete factors to promote atrophy by evaluating the effects of conditioned media (CM) from murine lung cancer cells and primary cultures of human lung tumor cells on cultured myotubes. We evaluated murine Lewis lung carcinoma (LLC) and KRASG12D cells, and primary cell lines derived from tumor biopsies from patients with lung cancer (hTCM; n = 6). In all experiments, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 71 publications
0
10
2
Order By: Relevance
“…in which the effect of murine and human lung tumour secreted factors on skeletal muscle was investigated. 44 Their report revealed that in fully matured C2C12 myotubes, myotube size and myosin heavy chain content were not affected by tumour‐derived factors. Altogether, these data do not support activation of the proteasome by E3‐ubiquitin ligases and subsequent myofibre atrophy as a direct effect of pancreas tumour‐derived factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…in which the effect of murine and human lung tumour secreted factors on skeletal muscle was investigated. 44 Their report revealed that in fully matured C2C12 myotubes, myotube size and myosin heavy chain content were not affected by tumour‐derived factors. Altogether, these data do not support activation of the proteasome by E3‐ubiquitin ligases and subsequent myofibre atrophy as a direct effect of pancreas tumour‐derived factors.…”
Section: Discussionmentioning
confidence: 98%
“…Although this contrasts with findings of other studies, 8,41,42 our data are in line with a recent study of Guigni et al . in which the effect of murine and human lung tumour secreted factors on skeletal muscle was investigated 44 . Their report revealed that in fully matured C2C12 myotubes, myotube size and myosin heavy chain content were not affected by tumour‐derived factors.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro models of lung cancer-associated cachexia that use 2D cultures of myotubes and conditioned medium from lung carcinoma cells have been described previously (62)(63)(64). One study using all human cells reported that myotubes showed a lack of atrophy when exposed to cancer cell-conditioned medium (63), perhaps due to the potential issues of a low concentration of tumor-derived factors in conditioned medium and the lack of a temporal change in signal, both of which are accounted for by the low-volume coculture in our microphysiological system. Furthermore, we demonstrated that incorporating drug-resistant tumor tissues in the model contributes to increased elaboration of TNF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, miRNAs, exosomes, proteins, or other small molecules could mediate this crosstalk. This finding importantly contradicts recent reports in other cancer types, where CM from cancer cells did not induce skeletal muscle mitochondrial deficits in vitro67 . This contrast suggests that different cancer types induce skeletal muscle dysfunction via different mechanisms, or perhaps that the small methodological differences between the two laboratories is responsible for the difference in results.…”
contrasting
confidence: 94%